Effect of a home-based inspiratory muscular training programme on functional capacity in patients with chronic COVID-19 after a hospital discharge: protocol for a randomised control trial (InsCOVID trial) - Julio Nuñez; Laura López; Cruz González; Patricia Palau; Eloy Domínguez; Clara Sastre; M Luz Martínez; Elvira Bondía; Crtstina Albiach (BMJ Open Respiratory Research, 2022)
Introduction Exercise intolerance and fatigue are the most common symptoms in patients with chronic COVID-19 after hospital discharge. Supervised exercise training programmes improve symptoms, but scarce research has been done on home-based exercise programmes on the maximal functional capacity for discharged symptomatic COVID-19 patients. This study evaluates whether a home-based inspiratory muscle training (IMT) programme improves maximal functional capacity in chronic COVID-19 after hospital admission.Methods and analysis This single-centre, assessor-blinded randomised controlled trial, powered for superiority, seeks to evaluate maximal functional capacity as the primary endpoint. A total of 26 eligible patients with a previous admission for acute respiratory syndrome coronavirus 2 pneumonia (>3 months after hospital discharge) will be randomised (1:1) to receive a 12-week programme of IMT versus usual care alone. A blinded assessor will measure outcomes at baseline and after the intervention (12 weeks). An analysis of variance will be used to compare continuous outcomes among the two-intervention groups. As of 21 March 2022, eight patients have been enrolled.Ethics and dissemination The research ethics committee (Comité Ético de Investigación con Medicamentos de l'Hospital Clínic Universitari de València) approved the protocol following the principles of the Declaration of Helsinki and national regulations (Approval Number: 021/226). Findings will be published in peer-reviewed journals and conference publications.Trial registration number NCT05279430.